2005
DOI: 10.1007/s00381-005-1172-y
|View full text |Cite
|
Sign up to set email alerts
|

Epidermoid cyst of the brain stem symptomatic in childhood

Abstract: We suggest that the symptoms of this present case appeared very early due to liquefaction of the cyst content with compression and displacement of the brain stem caudally. The recent infection process may predispose the pathological condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…1 While spontaneous remission of symptoms has been known to occur secondary to cystic rupture and decompression, this provides only temporary relief. 44,[76][77][78] Subtotal resection may lead to tumor recurrence, estimated to occur during an interval equal to the patient's age at initial symptom presentation plus nine months. 79,80 Earlier epidermoid recurrence is thought to derive from multiple residual clonogenic cells, chronic inflammation resulting in increased proliferation as occurs in normal skin, 79,81 or malignant transformation.…”
Section: Treatmentmentioning
confidence: 99%
“…1 While spontaneous remission of symptoms has been known to occur secondary to cystic rupture and decompression, this provides only temporary relief. 44,[76][77][78] Subtotal resection may lead to tumor recurrence, estimated to occur during an interval equal to the patient's age at initial symptom presentation plus nine months. 79,80 Earlier epidermoid recurrence is thought to derive from multiple residual clonogenic cells, chronic inflammation resulting in increased proliferation as occurs in normal skin, 79,81 or malignant transformation.…”
Section: Treatmentmentioning
confidence: 99%
“…4,14,24,43 Migration of embryonic ectodermal remnants along the Virchow-Robin spaces around the brain microvasculature. 11,13,43 This hypothesis can explain the occurrence of intrinsic brain stem epidermoid tumors even in the later part of the life.17,43,45 Ziyal et al 45 reported that the tumor extends from the cisternal space into the brain stem, and is usually demonstrated as an exophytic lesion in the ventral brain stem cisterns. Over a period, the brain parenchyma may cover the cyst contents and may give the appearance that the lesion is intra axial.…”
Section: Pathogenesis and Rationale For The Classifi Cationmentioning
confidence: 98%
“…4,24,31,43,45 The proliferation of pluripotent embryonic remnants along the otic and optic cerebral vesicles can explain the occurrence of the majority of cranial epidermoids either in Cerebello pontine angle (CPA) or sellar areas. 4,14,24,43 Migration of embryonic ectodermal remnants along the Virchow-Robin spaces around the brain microvasculature.…”
Section: Pathogenesis and Rationale For The Classifi Cationmentioning
confidence: 99%
See 2 more Smart Citations